Efficacy of imaginative vocal training for enhancing vocal awareness in non-professional singers - Federica Biassoni; Giulia Vismara; Martina Gnerre (PLoS ONE, 2025)
The objective of this study was to examine whether different types of mental-imagery training focused on the vocal apparatus can enhance awareness of the vocal tract and diaphragm (vocal awareness) in non-professional singers.Sixty participants with no singing education received one of three training conditions: following instructions based on 1) a description of the physiological changes that take place during phonation (physiological description), 2) imitating an action using the vocal apparatus (imitative action), and 3) a metaphorical narration. Imitative action and metaphorical narration were conceptualized as more imaginative forms of training. Vocal awareness was assessed with a questionnaire that participants completed before and after the training. The questionnaire measured three indices: vocal apparatus representation, vocal apparatus interoceptive awareness, and vocal self-regulation. Results showed that all three types of training program significantly enhanced vocal awareness, but imitative action and metaphorical narration were more effective for interoceptive awareness, and metaphorical narration was more effective for self-regulation. In conclusion, the two imaginative forms of training were more effective than physiological description for improving vocal awareness.